(untitled) (Experimental biology, 2015)
In this paper, applied to grapes cost-effective method of genotyping 6 microsatellite markers using the corresponding pairs of unlabeled specific primers and three universal oligonucleotides labeled with different fluorescent dyes. This technique is used for genotyping of several promising Kazakhstan varieties and their parental forms . Analysis conducted by researchers grapes used set of 6 markers and mikrosattelite: VVS2, VVMD5, VVMD7, VVMD27, ssrVrZAG62 and ssrVrZAG79 confirmed for Kazakhstan’s varieties parent-offspring relationship." The method will be used for genetic certification of grapevine varieties in Kazakhstan.